POSTPONEMENT OF DEBT PAYMENT OBLIGATIONS (PKPU) IN INDONESIAN BANKRUPTCY LAW: STRATEGIC APPROACH TO ADDRESSING BUSINESS CHALLENGES - Nainggolan, Bernard (UNISSULA, 2022)
This research aims to determine the potential for implementing Payment Postponement (PKPU) when the economy is sluggish and to find out the challenges faced by business entities. By using a normative juridical approach with a philosophical and conceptual perspective, this research reveals critical insights. These findings underscore the important relationship between PKPU and bankruptcy as a reasonable solution for debtors experiencing difficulties. However, in this solution there are latent risks that can be detrimental. Therefore, the debtor's careful behavior is very important in dealing with this dangerous situation. This research emphasizes that the option to carry out debt restructuring or financial restructuring carries relatively lower risks for debtors, thereby placing them in an advantageous position. Instead, PKPU appears as a viable solution, although it is best done as a last resort. This research highlights the dynamics that exist around the use of PKPU, highlighting the potential as well as the associated risks. The report advocates informed decision-making among debtors, by emphasizing the importance of choosing debt settlement strategies with the least risk.